Evaluation of the Vocational Education Program for Computer Engineering Networking and Computer Programming at the Dar El Ilmi Islamic Boarding School - Elhadi, Hafzan; Rahmi , Ulfia; Jasrial; Ridwan (Universitas Jambi, Indonesia, 2024)
This research aimed to determine the input, process, and output aspects in finding gaps in the Vocational Program at the Dar El Ilmi Islamic Boarding School Payakumbuh against the regulations of Minister of Religion Decree Number 347 of 2022 concerning Guidelines for Curriculum Implementation in Madrasas. It was qualitative research. The results indicated the vocational education program at the Dar El Ilmi Islamic Boarding School Payakumbuh has been running well according to existing regulations. However, there were several gaps, including the input evaluation aspect of the vocational program at the Dar El Ilmi Islamic Boarding School. The evaluation aspect of the vocational program process at the Dar El Ilmi Islamic Boarding School was very good, namely 96.29%, although a gap was found, namely 3.71%. The evaluation aspect of the vocational program output at the Dar El Ilmi Islamic Boarding School was very good, namely 97.5%, although a gap was found of 2.5%.